Financial Contagion in European Equity Markets: Evidence from the US Subprime and the Eurozone Crises - Kumar, Ashish; Khanna, Swati; Dhingra, Sanjay; Sinha, Neena (Indian Journal of Finance, 2022)
The study explored the financial contagion between the five European stock markets (Germany, Belgium, France, Netherlands, and Spain) and the impact of the US subprime crisis and Eurozone crisis on it by employing multivariate DCC-GARCH methodology. The dynamic conditional correlation coefficient between Germany and other European markets was statistically significant for the period under review. The rise in the value of the conditional correlation coefficient was more evident during the US subprime crisis period, which signified the impact of this crisis on the financial interdependence of the European stock markets. But not much influence of the Eurozone crisis was observed on the dispersion of returns for all the markets, which was an important finding. The mechanism of rolling regression also corroborated these results. The study also validated the presence of financial contagion between the stock markets (except the Netherlands) during the US subprime crisis period. In contrast, the effect of the Eurozone crisis on financial contagion was significant only for Spain and Belgium. Further, the strength of financial contagion was highest for the stock market of Spain, followed by Belgium, and the least for the Netherlands. The timid reaction of the stock market of the Netherlands reflected that it could be a good choice for portfolio diversification during periods of crisis for investors. Further, governments and other regulators can learn from these findings and formulate appropriate policies to absorb the financial shocks coming from foreign markets, especially during the crisis period.